URGENSINYA PERANAN PEMERINTAH DAERAH KABUPATEN KAITANNYA DENGAN ASAS KEBEBASAN BERKONTRAK DALAM PERJANJIAN INNOMINAT DALAM JENIS WARALABA - SANTHOMAL, EVI RINDHA (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACT Basically the Freedom of Contract principle contained in Article 1338 of the Civil Code has given wide impartiality to the franchise agreement in Indonesia. The implications that occur can lead to an unhealthy business competition as well as monopolistic acts as listed in Law No. 5 of 1999, considering the Eramart franchise agreement in Indonesia does not have a regulation that regulates in detail from all aspects. While the Franchise Agreement which uses the Principle of Freedom of Contract In article 1338 of the Civil Code has granted the parties the freedom to make agreements without the strict limitation of existing regulations. As most of the Franchisees, both Franchisors and Franchisees who want Franchise / Franchise agreements in Indonesia are not specifically regulated by the government, so the Franchise Business can develop well in an economy. Freedom of contract in the Eramart Franchise Agreement is in principle not absolute, given the role of government in terms of the Franchise Procedure in Indonesia. Such as the Franchise registration procedure and the issuance of Franchise Business Registration License at the Ministry of Domestic Trade. Use of domestic goods. As a supplier or a franchise party so get improve and develop small and medium enterprises in Indonesia. Keywords : Franchise, Innominat Agreement, Freedom of Contract